SNAr Reactions on 2-Amino-4,6-dichloropyrimidine-5-carbaldehyde (2022)
We report the experimental results of unexpected aromatic nucleophilic substitution reaction products on 2-amino-4,6-dichloropyrimidine-5-carbaldehyde. The isolated compounds are products of amination, solvolysis, and condensation processes under mild and environmentally friendly conditions, due to the influence of structural factors of the starting pyrimidine and a high concentration of alkoxide ions. This method allows the building of pyrimidine-based compound precursors of N-heterocyclic systems.